Documentary research on social innovationin health in Latin America (2020)
Background: Identifying social innovation in health initiatives, promoting quality of life through them, and transforming current health conditions demand the knowledge, comprehension and appropriation of the theoretical and methodological developments of this concept. Academic developments in social innovation have mainly occurred in and been documented for English-speaking countries, although relevant experiences have been implemented in Latin America. In this article, we describe and analyze how social innovation in health is being approached and understood in this region. Main text: To identify the theoretical and methodological developments of social innovation in health between 2013 and 2018, a scoping review with a mixed approach was carried out. Eighty texts in English, Spanish and Portuguese were selected for a process of reflexive analysis of intra and intertextual reading. The approaches identified in the studied initiatives were complementary. The most applied approaches were innovation in health, technological innovation in health and social innovation, each with twelve publications, and social innovation in health and ecohealth with ten and seven publications respectively. The approaches showed a general interest in reaching the goals of the Sustainable Development Goals (SDGs), the Alma Ata Declaration and the Ottawa Letter.